2013
DOI: 10.1016/j.ijcard.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Coronary Heart Disease Mortality declines in the Republic of Ireland, 1985–2006

Abstract: Background: Consistent declines in coronary heart disease (CHD) death rates have been previously observed in Ireland since1985. Aims & Methods: To use the previously validated Irish IMPACT CHD mortality model to further examine the subsequent CHD mortality falls from 1985 through to 2006, and to determine the contribution of risk factor changes and "evidence based" treatments to this decline by age and gender. Results: CHD mortality rates fell by 68% in men (63% in 65-84 years) and by 69% in women (66% in 65-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Improvement in prescribing rate is similarly observed in other countries [7, 25, 26] and is believed to contribute to improvement in NSTEMI outcomes [27, 28]. Similar trend has been described for STEMI patients [18].…”
Section: Discussionsupporting
confidence: 70%
“…Improvement in prescribing rate is similarly observed in other countries [7, 25, 26] and is believed to contribute to improvement in NSTEMI outcomes [27, 28]. Similar trend has been described for STEMI patients [18].…”
Section: Discussionsupporting
confidence: 70%
“…3 This decline in cardiovascular mortality is attributed to a combination of improved treatment uptake (40%) and an improvement in risk factors (48%). 4 Hypertension is a leading modifiable risk factor for CVD and estimated to be responsible for at least 45% of ischaemic heart disease mortality and 51% of total stroke mortality globally. 5 The burden of hypertension is increasing worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent updated modelling study of CHD mortality decline in Ireland between 1985 and 2006, similar trends were observed. However, in the latter study, deteriorating trends in obesity and diabetes prevalence were observed 4. For many population-level interventions, the first step is to quantify the effectiveness of such interventions to make judgements on the allocation of finite health resources.…”
Section: Introductionmentioning
confidence: 90%
“…Details of the Irish CHD IMPACT model were published earlier 3 4. In brief, the food policy IMPACT model is an extension and adaptation of the original CHD IMPACT model and is conceptually similar to the IMPACT food model published recently 5.…”
Section: Methodsmentioning
confidence: 99%